2022
DOI: 10.1109/ojemb.2022.3215726
|View full text |Cite
|
Sign up to set email alerts
|

A Biorealistic Computational Model Unfolds Human-Like Compliant Properties for Control of Hand Prosthesis

Abstract: System overview of a virtual prosthetic hand with a biorealistic neuromorphic reflex controller, whose inputs are α motor command, γs and γd commands. B.Block diagram of the integrated virtual hand system. It consists of a tendon-driven virtual hand, a pair of antagonistic muscles with the biorealistic controller and a sensory feedback system. Force perturbations can be applied at the fingertip, or at the tendon of flexor/extensor muscles in perturbation experiments. C. Simulation results unveil that the virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…Figure 4 depicted the feasibility of adjusting reflexive alpha motor commands upon detection of nociceptive temperature. Results revealed that these alpha motor command adjustments could generate well-behaved muscle forces, which were consistent with the previous research ( Niu et al, 2021 ; Zhang Z. et al, 2022 ). This withdrawal reflex originated in the spinal cord and was a demonstration of the short-latency spinal reflex, which was a subconscious action to unpredictable perturbation ( Andersen, 2007 ; Zangrandi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 4 depicted the feasibility of adjusting reflexive alpha motor commands upon detection of nociceptive temperature. Results revealed that these alpha motor command adjustments could generate well-behaved muscle forces, which were consistent with the previous research ( Niu et al, 2021 ; Zhang Z. et al, 2022 ). This withdrawal reflex originated in the spinal cord and was a demonstration of the short-latency spinal reflex, which was a subconscious action to unpredictable perturbation ( Andersen, 2007 ; Zangrandi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, normalized sEMG was used to represent the alpha motor command, with the sEMG normalized to 0 and 1 when the subject was resting and exerting maximum voluntary contraction force, respectively. More detailed information was published in previous research ( Xie et al, 2022 ; Zhang et al, 2022b , Zhang Z. et al, 2022c ).…”
Section: Methodsmentioning
confidence: 99%
“…Designing electronic prosthetics with a greater biological realism is essential for improving their compatibility with the sensory and motor nervous systems [55]. Thus, a deeper understanding of human neuromuscular reflex replicas is required, including emerging qualities such as human-like compliance, force and position control, as well as adaptive stiffness [56]. These qualities will enhance the compatibility of neuroprosthetics with the human body.…”
Section: Discussionmentioning
confidence: 99%
“…In artificial systems, the optimalities will likely not fully overlap with those found in the biological system (Dideriksen et al 2012). Finally, the approach presented here may have useful implications for neuroprosthetics (Unal et al 2018, Lan et al 2023, Zhang et al 2022.…”
Section: Future Researchmentioning
confidence: 92%